Experimental study of improving the efficiency of photovoltaic cells by using various angles of pneumatic routers - Jaber, Ayad Jasim; Abd Balla, Hyder Hassan; Aboaltabooq, Mahdi Hatf Kadhum; Sapit, Azwan (Alpha Publishers, 2019)
The photovoltaic (PV) panels‟ chief precedence and abundant concern is the electricity‟s production. Moreover, the conversion of solar energy into electricity relies upon the operation of solar cell temperature in an upsurge in performance with temperature reductions. This paper describes the development of a new type of cooling of hybrid photovoltaic (PVT) cells, The experimental study presents a method to the decrease in photovoltaic panels‟ temperature with the usage of air cooled heat sinks, our search results were the electrical efficiency values increased from 2.5% to 7%, while the temperature values the PV panel decreased from 5.2% to 15%, at air mass flow rates of 0.116and 0.466kg/s, respectively. For this purpose, the trial installations were manufactured in Iraq at the Technical University of AlFurat Al-Awsat. The goal of this research was to distinguish the solar panel‟s electrical behavior to progress the advancement in the photovoltaic installations‟ design retained in conforming the less operating temperatures that will accurate and converse the manufactured impacts on the effectiveness through low operating temperatures while using the fossil fuel usage as well as the consumption of electricity in several applications.